2021
DOI: 10.32859/era.22.10.1-18
|View full text |Cite
|
Sign up to set email alerts
|

Putative Anthelmintic Plants Used in Traditional Medicine System of Kokrajhar District, India

Abstract: Background: Traditional medicine (TM) is a common practice among tribal communities of India. The present study has been designed to collect the ethnomedicinal plants used by the Bodo community of Kokrajhar district of India traditionally consumed to cure helminth infection.Methods: A total of 54 villages were surveyed from the Kokrajhar district. Twenty adjacent villages were taken as a cluster, and one informant was interviewed face-to-face with the help of a readymade questionnaire. Traditional knowledge sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
1
1
1
Order By: Relevance
“…Plants with high RFC values, on the other hand, are endangered and should be prioritized for conservation and long-term usage (Amjad et al 2020). The results of this study were different from those by Swargiary et al (2021) who reported Andrographis paniculata, Alstonia scholaris, Ananas comosus, and Azadirachta indica to be the dominant anthelmintic plants. Despite having a low RFC value of 0.013 during the investigation, Flemingia vestita (Das et al 2009;Toner et al 2008), Zingiber offficinale (Ghafar et al 2021;Kiambom et al 2021;Toulah et al 2019), Azadirachta indica (Ibekwe 2019;Salma et al 2021;Yamson et al 2019), and Allium sativum (Azra et al 2019;Luce 2019;Shirgholami et al 2021) plants' tubers have been widely explored as a source of anthelmintic chemicals against helminths and their important proteins (enzymes).…”
Section: Species Relative Frequency Of Citation (Rfc)contrasting
confidence: 90%
“…Plants with high RFC values, on the other hand, are endangered and should be prioritized for conservation and long-term usage (Amjad et al 2020). The results of this study were different from those by Swargiary et al (2021) who reported Andrographis paniculata, Alstonia scholaris, Ananas comosus, and Azadirachta indica to be the dominant anthelmintic plants. Despite having a low RFC value of 0.013 during the investigation, Flemingia vestita (Das et al 2009;Toner et al 2008), Zingiber offficinale (Ghafar et al 2021;Kiambom et al 2021;Toulah et al 2019), Azadirachta indica (Ibekwe 2019;Salma et al 2021;Yamson et al 2019), and Allium sativum (Azra et al 2019;Luce 2019;Shirgholami et al 2021) plants' tubers have been widely explored as a source of anthelmintic chemicals against helminths and their important proteins (enzymes).…”
Section: Species Relative Frequency Of Citation (Rfc)contrasting
confidence: 90%
“…As reported by many other kinds of literature, most traditional formulations use leave as the major ingredient. [37][38][39] Similarly to other studies, we also documented herbs as the highest used mosquito repellant plants by the fringe villagers of MNP. [40,41] The mode of use to repel away the mosquitoes were mostly smoking.…”
Section: Discussionsupporting
confidence: 80%
“…E. neriifolia was used efficiently in a blend with several other herbal plants to treat helminthiasis. Swargiary also listed 64 plants that were used to treat helminthiasis in traditional medicine system of India [ 101 ].…”
Section: Antimicrobial Activities Of E Neriifolia ...mentioning
confidence: 99%